Implementasi Algoritme Enkripsi Homomorphic Schmidt-Takagi Versi 2 pada Sistem E-Voting - Ivan Faturahman; Ari Kusyanti; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Securing ballots is an important aspect in upholding the principle of trust in e-voting, which means that public must have confidence in each instruments which form an e-voting. Fraud by the administrator can not be handled by implementing an encryption algorithm alone, because on many e-voting systems, administrator has task to do the decryption. Fraud on ballots from administrator can be avoided by not providing data ballots directly to administrator, this can be done by tallying the ballot. This method in cryptography can be done by using an encryption algorithm with homomorphic property. The new variation algorithm of Schmidt-Takagi algorithm found by three mathematicians and computer experts from the Tokyo Institute of Technology namely, Takato Hirano, Koichiro Wada, and Keisuke Tanaka has a homomorphic property. This algorithm was chosen because it is said to be faster in the encryption and decryption process than the Damgard-Jurik algorithm. At the end of implementing the algorithm, the average time taken by the system to encrypt with the majority of votes 1; 10; and 100 are 2,682ms, 2,893ms and 2,976ms. Then the average time for decryption with the same scenario are 1,459ms, 1,51ms, and 2,775ms.